YouTube as a source of information on penile prosthesis. (14th September 2021) - Capece, Marco; Di Giovanni, Angelo; Cirigliano, Lorenzo; Napolitano, Luigi; La Rocca, Roberto; Creta, Massimiliano; Califano, Gianluigi; Crocetto, Felice; Collà Ruvolo, Claudia; Celentano, Giuseppe; Palmieri, Alessandro
Abstract: The purpose of this study is to evaluate the quality of information on YouTube regarding penile prosthesis. We searched the term 'penile prosthesis' on YouTube recording the first 100 video links. Each video was analysed by three evaluators through the validate Patient Education Materials Assessment Tool (PEMAT), the DISCERN quality criteria for consumer health information and a misinformation assessment tool specifically created for this subject. All the videos were viewed 10′011′232 times. Median duration time was 5′13″ (IQR = 7′25″–1′58″). Sixty‐eight per cent were nonsurgical videos and 32% of them contained surgical procedures. Most of the videos were uploaded by Private Companies (51%). Videos were primarily directed at patients (73 of 100 videos). The mean PEMAT understandability score was 57.8% ± 19.2%, the actionability score was 0% (IQR = 33%–0%). The median DISCERN score was 26 (IQR = 30–21). None of the videos provided a complete patients' information and the overall mean misinformation score was 3.21 ± 2.24. Based on our data, video's quality according to PEMAT and DISCERN score is mostly poor. Furthermore popularity does not correlate with the quality of the videos, and most of them fail to provide adequate patient's information.